Confinement induces oxidative damage and synaptic dysfunction in mice - Li, Nuomin; Wang, Hao; Xin, Shuchen; Min, Rui; Zhang, Yongqian; Deng, Yulin (Frontiers in Physiology, 2022)
A confined environment is an enclosed area where entry or exit is highly restricted, which is a risk factor for a work crew’s mental health. Previous studies have shown that a crew is more susceptible to developing anxiety or depression in a confined environment. However, the underlying mechanism by which negative emotion is induced by confinement is not fully understood. Hence, in this study, mice were retained in a tube to simulate short-term confinement. The mice exhibited depressive-like behavior. Additionally, the levels of H2O2 and malondialdehyde in the prefrontal cortex were significantly increased in the confinement group. Furthermore, a label-free quantitative proteomic strategy was applied to analyze the abundance of proteins in the prefrontal cortex of mice. A total of 71 proteins were considered differentially abundant proteins among 3023 identified proteins. Two differentially abundant proteins, superoxide dismutase [Mn] and syntaxin-1A, were also validated by a parallel reaction monitoring assay. Strikingly, the DAPs were highly enriched in the respiratory chain, oxidative phosphorylation, and the synaptic vesicle cycle, which might lead to oxidative damage and synaptic dysfunction. The results of this study provide valuable information to better understand the mechanisms of depressive-like behavior induced by confined environments.